[BP.09.07] CARDIORESPIRATORY FITNESS AND STROKE INCIDENCE IN HYPERTENSIVE OVERWEIGHT AND OBESE PATIENTS. (September 2017) - Pittaras, A.; Faselis, C.; Narayan, P.; Doumas, M.; Kallistratos, E.; Grassos, H.; Papavasiliou, M.; Kouremenos, N.; Kyfnidis, K.; Tsioufis, C.; Manolis, A.J.; Kokkinos, P.
Abstract : Objective: Stroke incidence in hypertension and obesity increase significantly higher in hypertensive patients compared to normotensive subjects. Cardiorespiratory fitness (CRF) is associated with a more favorable cardiovascular health. The CRF-stroke incidence association in hypertensive patients has not been fully explored. Design and method: We assessed the hypothesis that CRF is inversely and independently associated with stroke incidence in hypertensive patients. From 1985 to 2014, we identified 9, 885 hypertensive overweight or obese patients (mean age: 59 ± 10 years) with a normal response to an exercise tolerance test (ETT) and no prior history of stroke. We established five fitness categories based on age-stratified quintiles of peak metabolic equivalents (MET) achieved: Least-Fit (4.4 ± 1.2 METs; n = 2, 032); Low-Fit (5.9 ± 1.1; n = 2, 347); Moderate-Fit (7.2 ± 1.1 METs; n = 2, 152); Fit (8.4 ± 1.2 METs; n = 2, 060); and High-Fit (11.0 ± 2.0 METs; n = 1, 317). A multivariable Cox proportional hazards model was used to estimate hazard ratios (HR) and 95% confidence intervals [CI] for incidence of stroke across fitness categories. The model was adjusted for age, resting blood pressure, atrial fibrillation, gender, race, other cardiac risk factors, alcohol dependence and medications. The Least-fit category was used as the reference group. Results: During follow-up (median = 11.5 years; 117, 429 person-years), 517 individuals (4.4 events per 1, 000 person-years) developed stroke. The risk for stroke was 6% lower for each 1-MET increase in exercise capacity (HR = 0.94, CI: 0.90–0.98; p < 0.004). When considering fitness categories, stroke risk was lower by 28% (HR = 0.72; CI: 0.61–0.99) for the Low-fit individuals and approximately 34% for the Moderate-fit, Fit and High-Fit (HR = 0.66; CI: 0.49–0.90). Conclusions: Increased CRF was inversely related to stroke incidence in hypertensive patients. The association was independent and graded.